Metabolic responses at various intensities relative to critical swimming velocity - Toubekis, A. G.; Tokmakidis, Ss P. (The Journal of Strength and Conditioning Research, 2013)
To avoid any improper training load, the speed of endurance training needs to be regularly adjusted. Both the lactate threshold (LT) velocity and the velocity corresponding to the maximum lactate steady state (MLSS) are valid and reliable indices of swimming aerobic endurance and commonly used for evaluation and training pace adjustment. Alternatively, critical velocity (CV), defined as the velocity that can be maintained without exhaustion and assessed from swimming performance of various distances, is a valid, reliable, and practical index of swimming endurance, although the selection of the proper distances is a determinant factor. Critical velocity may be 3-6 and 8-11% faster compared with MLSS and LT, respectively. Interval swimming at CV will probably show steady-lactate concentration when the CV has been calculated by distances of 3- to 15-minute duration, and this is more evident in adult swimmers, whereas increasing or decreasing lactate concentration may appear in young and children swimmers. Therefore, appropriate corrections should be made to use CV for training pace adjustment. Findings in young and national level adult swimmers suggest that repetitions of distances of 100-400 m, and velocities corresponding to a CV range of 98-102% may be used for pacing aerobic training, training at the MLSS, and possibly training for improvement of VO2max. Calculation of CV from distances of 200-400, 50-100-200-400, or 100-800 m is an easy and practical method to assess aerobic endurance. This review intends to study the physiological responses and the feasibility of using CV for aerobic endurance evaluation and training pace adjustment, to help coaches to prescribe training sets for different age-group swimmers.